(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This paper deals with the opus of the relatively unexplored writer Vera Obrenović-Delibašić (1906), who participated in the Bosnian Herzegovinian literary life between two world wars by writing mostly poetry and short stories. After the war, she published novels which were focused on people’s uprising and antifascist fight (Kroz Ničiju Zemlju in 1948 and 1959, Višnja iz Ničije Zemlje in 1971), as well as short stories (Zore nad mahalama in 1955). It is precisely this prose and the narrative of revolution and the revolutionary times that this paper will focus on, with the aim of exploring the story of the national liberation struggle through the issue of the emancipatory potential of her stories and the (r) evolutions they represent. The symbolic discourse of reality of a time, an ideology, a culture, society and history is questioned in the paper. The question that is being asked is: Does this prose set in motion, by narrating a revolution, possible scenarios of emancipation of the individual from the patrilinear community which, in its antifascist aims, revolutionises its ways of life? And if so, what models of freedom, truth or justice does it offer when it comes to women’s position in that world? Is there such a representation to be found at all in this prose? In other words: How are models of gender, home, homeland, and freedom represented in the prose of Vera Obrenović-Delibašić when a woman’s name stands next to these formulas of meaning?